Friedrich Dürrenmatt und das Risiko der exzessiven Abstrusität. Achterloo: eine fast unmögliche Lektüre - Dragos Carasevici (Journal of Humanistic and Social Studies, 2014)
An objective perspective on the Achterloo “spiral”, a term used by Lutz Tantow so as to refer to the four versions of Dürrenmatt’s last dramatic text, must take into account, on the one hand, the ideatic and structural complexity of this work, and, on the other hand, the reception difficulties such complexity entails. One reception difficulty regards the “mobility” of this text: its constant processing motivated by Dürrenmatt’s desire to improve the staging means, led to four versions (out of which three were published), one more problematic than the other. Another reception difficulty, which actually represents the core aspect of our study, regards the dense intertextual network constructed in all versions by means of the collage technique. In fact it is a huge collage composed of three interdependent collages: one of them includes apparently unrelated historical figures, another one deals with fictional figures of universal literature (where some characters baffle) and, finally, a third collage includes motifs and themes characteristic of Dürrenmatt’s dramatic work. If these difficulties represent a challenge for the fields of Philology and Theatre, they confront the public with an almost impenetrable wall, a consequence of excessive abstruseness which, especially in the case of a play, may eclipse any other qualities of the text.